Burden of Serious Fungal Infections in India. (26th December 2022) - Ray, Animesh; Aayilliath K, Adarsh; Banerjee, Sayantan; Chakrabarti, Arunaloke; Denning, David W
Abstract: Background: Fungal disease is frequent in India, but its incidence and prevalence are unclear. This review aims at defining the frequency or burden of various fungal infections in India. Methods: A systematic review of the literature on the PubMed, Embase, and Web of Science (WOS) databases was conducted using appropriate search strings. Deterministic modeling determined annual incidence and prevalence estimates for multiple life- and sight-threatening infections with significant morbidity. Results: Literature searches yielded >2900 papers; 434 papers with incidence/prevalence/proportion data were analyzed. An estimated 57 251 328 of the 1 393 400 000 people in India (4.1%) suffer from a serious fungal disease. The prevalence (in millions) of recurrent vulvovaginal candidiasis is 24.3, allergic bronchopulmonary aspergillosis is 2.0, tinea capitis in school-age children is 25, severe asthma with fungal sensitization is 1.36, chronic pulmonary aspergillosis is 1.74, and chronic fungal rhinosinusitis is 1.52. The annual incidence rates of Pneumocystis pneumonia (58 400), invasive aspergillosis (250 900), mucormycosis (195 000), esophageal candidiasis in HIV (266 600), candidemia (188 000), fungal keratitis (1 017 100), and cryptococcal meningitis (11 500) were also determined. Histoplasmosis, talaromycosis, mycetoma, and chromoblastomycosis were less frequent. Conclusions: India's fungal burden is high and underappreciated in clinical practice. Abstract : This systematic review, synthesizing data from 434 published papers, estimates that 60 million Indians (4.1%) are afflicted by a serious fungal disease. Tinea capitis and recurrent VVC account for 49 million, with chronic pulmonary aspergillosis and fungal rhinosinusitis affect over 3 million.